The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zheng, Zhong-Bing; Yang, Yu; Liu, Jun; Zhou, Ming-Cheng; Li, Ju-Hua; Tang, Long-Jiang; Nie, Hai-Long; Chen, Kang-Sheng; Liu, Feng; He, Xiang-Ning; Lu, Zhi-Yuan (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na+-K+-ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.